Vitamin D deficiency in head and neck cancer patients – prevalence, prognostic value and impact on immune function. (2nd September 2018) - Bochen, Florian; Balensiefer, Benedikt; Körner, Sandrina; Bittenbring, Jörg Thomas; Neumann, Frank; Koch, Armand; Bumm, Klaus; Marx, Anke; Wemmert, Silke; Papaspyrou, Georgios; Zuschlag, David; Kühn, Jan Philipp; et al.
ABSTRACT: Vitamin D deficiency is frequently observed in human cancer patients and a prognostic relevance could be shown for some entities. Additionally, it is known that vitamin D can stimulate the patients' antitumor immunity. However, valid epidemiological data for head and neck squamous cell carcinoma (HNSCC) patients are sparse and functional studies on a possible connection between vitamin D and the patients' immune system are missing. 25-OH vitamin D serum levels were analyzed in 231 HNSCC patients and 232 healthy controls and correlated with clinical data and patient survival. Intra- and peritumoral infiltration with T-cell, NK-cell and macrophage populations was analyzed in 102 HNSCC patients by immunohistochemistry. In 11 HNSCC patients, NK-cells were isolated before and after vitamin D substitution and analyzed for their cytotoxic activity directed against a HNSCC cell line. Vitamin D serum levels were significantly lower in HNSCC patients compared with healthy controls. Low vitamin D levels were associated with lymphatic metastasis and a negative HPV status and were a significant predictor of poor overall survival. HNSCC patients with severe vitamin D deficiency showed significantly altered intra- and peritumoral immune cell infiltrate levels. After vitamin D substitution, the patients' NK cells showed a significant rise in cytotoxic activity. Taken together, we could show that Vitamin D deficiency is highly prevalent in HNSCC patients and is a predictor of poor survival. Vitamin D substitution used as an adjuvant in immune therapies such as cetuximab and nivolumab treatment could support antitumorigenic immune responses, thus contributing to the improvement of the patients' prognosis in the context of a multimodal therapy.